Measurement of nurses' workload in an oncology outpatient clinic - Souza, Célia Alves de; Jericó, Marli de Carvalho; Perroca, Marcia Galan (Revista da Escola de Enfermagem da USP, 2014)
The growing demand and the degree of patient care in oncological outpatient services, as well as the complexity of treatment have had an impact on the workload of nurses. This study aimed at measuring the workload and productivity of nurses in an oncological outpatient service. An observational study using a work sampling technique was conducted and included seven nurses working in an oncological outpatient service in the south-eastern region of Brazil. A total of 1,487 intervention or activity samples were obtained. Nurses used 43.2% of their time on indirect care, 33.2% on direct care, 11.6% on associated activities, and 12% on personal activities. Their mean productivity was 88.0%. The findings showed that nurses in this service spend most of their time in indirect care activities. Moreover, the productivity index in this study was above that recommended in the literature.